Brain Gray Matter Atrophy after Spinal Cord Injury: A Voxel-Based Morphometry Study - Chen, Qian; Zheng, Weimin; Chen, Xin; Wan, Lu; Qin, Wen; Qi, Zhigang; Chen, Nan; Li, Kuncheng (Frontiers in Human Neuroscience, 2017)
The aim of this study was to explore possible changes in whole brain gray matter volume (GMV) after spinal cord injury (SCI) using voxel-based morphometry (VBM), and to study their associations with the injury duration, severity, and clinical variables. In total, 21 patients with SCI (10 with complete and 11 with incomplete SCI) and 21 age- and sex-matched healthy controls (HCs) were recruited. The 3D high-resolution T1-weighted structural images of all subjects were obtained using a 3.0 Tesla MRI system. Disease duration and American Spinal Injury Association (ASIA) Scale scores were also obtained from each patient. Voxel-based morphometry analysis was carried out to investigate the differences in GMV between patients with SCI and HCs, and between the SCI sub-groups. Associations between GMV and clinical variables were also analyzed. Compared with HCs, patients with SCI showed significant GMV decrease in the dorsal anterior cingulate cortex, bilateral anterior insular cortex, bilateral orbital frontal cortex (OFC), and right superior temporal gyrus. No significant difference in GMV in these areas was found either between the complete and incomplete SCI sub-groups, or between the sub-acute (duration <1 year) and chronic (duration >1 year) sub-groups. Finally, the GMV of the right OFC was correlated with the clinical motor scores of left extremities in not only all SCI patients, but especially the CSCI subgroup. In the sub-acute subgroup, we found a significant positive correlation between the dACC GMV and the total clinical motor scores, and a significant negative correlation between right OFC GMV and the injury duration. These findings indicate that SCI can cause remote atrophy of brain gray matter, especially in the salient network. In general, the duration and severity of SCI may be not associated with the degree of brain atrophy in total SCI patients, but there may be associations between them in subgroups.